“Virtual Nagging”: Comprehension-based external regulation and success support for online learners - Semingson, Peggy; Owens, Dana; Kerns, William (2020)
Recent research and literature champions the power of nudge emails to coax students to make positive choices for their learning (Cavanagh & Eastham, 2019). This roundtable session and paper n expands on this concept more broadly and provides a comprehensive overview on the literature of external regulation for helping online learners to stay organized, focused, motivated, and “on top of” readings and assignments within an online course. As literacy teacher educators, we encourage the use of comprehension-focused overviews to help students fully understand the scope of tasks at the course level and the module level. Due to the challenging nature of distance and the need to stay on track with the pace of distance learning, instructors need to be able to communicate and support students in a variety of ways using language-based virtual outreach. We deem this as “virtual nagging” due to our experiences with virtual communications outreach in an all online master’s level literacy teacher education program. We provide key
Keywords: Distance/Flexible Education; Instructional Design; ⛔ No DOI found